Integration time conversion methods for Multi Precipitation Estimate rain maps - Hafiz Basarudin; Tengku Azita Tengku Aziz; Abdul Halim Ali; Muhammad Ismail Sulaiman; Aizat Faiz Ramli (Journal of Engineering Technology, 2016)
Rain fade is a phenomenon where rainfall causes radio signal operating at Ka or Ku Band frequencies to suffer signal degradation. To resolve this, radio engineers use annual rainfall rate distribution with 1 minute integration time to plan and design radio networks and assign appropriate fade margin. This paper aims to study the performance and impact of using several models to convert different integration times of measured rainfall rate annual distribution to 1 minute integration time. The models that will be covered in this paper are Burgueno et al, Segal, Joo et al and ITU-R 837 model for Multi Precipitation Estimate rain maps product. Comparison with rain gauge data collected in Malaysia will also be presented for further validation.